21st century astronomy - Hester, Jeffrey S.; Burstein, david; Blumenthal, George; Greeley, Ronald; Smith, Bradford; Voss, Howard G. (W. W. Norton & Company, 2007)
Sadržaj: 1. Why learn astronomy? ; 2. Patterns in the sky - motions of Earth ; 3. Gravity and orbits - a celestial ballet ; 4. Light ; 5. The tools of the astronomer ; 6. A brief history of the solar system ; 7. The terrestrial planets and Earth's moon ; 8. Atmospheres of the terrestrial planets ; 9. Worlds of gas and liquid - the giant planets ; 10. Gravity is more than Kepler's law ; 11. Planetary moons and rings, and dwarf planets ; 12. Asteroids, meteorites, comets, and other debris ; 13. Taking the measure of stars ; 14. A run-of-the-Mill G Dwarf: our Sun ; 15. Star formation and the interstellar medium ; 16. Stars in the slow lane ; 17. Live fast, die young ; 18. Galaxies ; 19. The Milky way - a normal spiral galaxy ; 20. Our expanding Univrese ; 21. The origin of structure